Effects of hall current on MHD orthogonal flow impinging on a wall with suction or blowing - Azram, Mohammad; Zaman, Haider; Ibrahim, M. (Publications International, 2014)
In this paper, we have studied the effects of Hall current on magnetohydrodynamic (MHD)orthogonal flow impinging on a wall with suction or blowing. We have used the homotopy analysis method(HAM) to obtain the complex explicit analytic solution of the emerging non-linear differential equation. The diagonal Pade approximants are used to analyze the essential behavior of F(y) and to determine the initial slope F′(0) . Tables. 1 and 2 are constructed and discussed for initial slope F′(0) and for wall shear stress F′′(0) , respectively. Convergence of the complex solution is also discussed with the help of h − curves and interval of convergence is also found.